1996
DOI: 10.1007/s001090050027
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion receptors in malignant transformation and dissemination of gastrointestinal tumors

Abstract: Changes in the expression and function of adhesion molecules on the surface of cancer cells are important characteristics in the development of gastrointestinal malignancies and might be used in the future as prognostic factors or as new targets for diagnostic and therapeutic approaches. In esophageal cancer a down-regulation of the E-cadherin receptor and the cytoplasmic protein alpha-catenin is associated with tumor dedifferentiation, infiltrative growth and lymph-node metastasis. In gastric cancer a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 0 publications
3
26
0
4
Order By: Relevance
“…Abnormalities of E-cadherin expression have been described in colorectal carcinoma [28] and have been correlated with increased invasiveness, metastatic potential and poor patient prognosis in this tumor type [29] . Recent research showed that E-cadherin expression was significantly lower in the de novo group tissue than that in the prudent group [30,31] . In the present study, by Western blotting analysis, we also confirmed that LST-R1 cells have a prominent lower expression of E-cadherin than that in several other cell lines.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Abnormalities of E-cadherin expression have been described in colorectal carcinoma [28] and have been correlated with increased invasiveness, metastatic potential and poor patient prognosis in this tumor type [29] . Recent research showed that E-cadherin expression was significantly lower in the de novo group tissue than that in the prudent group [30,31] . In the present study, by Western blotting analysis, we also confirmed that LST-R1 cells have a prominent lower expression of E-cadherin than that in several other cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Twenty-four hours later, the numbers of LST-R1 cells invading the membrane were significantly higher (179.3 ± 40 cells/well) than those of lovo (139.3 ± Table 1. [30],-3 [9],der(3)del(p12)t(2;3)(q21;q11) [21],-3 [9],der(4)t(4;10)(q11;p11) [30],d er(4)dup(14)(q22q31)t(4;14)(q?;q?) [9],der(4)t(3;4)(p21;p16)dup(14)(q22 q31)t(4;14)(q?;q?)…”
Section: The Invasion Ability Of Lst-r1 In Vitromentioning
confidence: 99%
See 3 more Smart Citations